Análisis crítico para demostrar la contradicción entre trabajo y capital en el discurso del desarrollo del Plan Nacional para El Buen Vivir 2009-2013 - Pazmiño Vásquez, Carlos Eduardo (2013)
This investigation provides a critical analysis of the discourse of development of the ―Plan Nacional para el Buen Vivir 2009-2013‖ to demonstrate the contradiction between labor and capital -characteristic of capitalist societies-, as Ecuadorian society is oriented to a bourgeois modernization process, whose purpose is to maintain capitalist operation under a ―revolutionary‖ discourse. On this stage the tendency XXI century stands as new step in the capitalism after the neoliberal crisis, without overshooting the capitalist model of accumulation, XXI century tendency represents the "new" revisionism and eclecticism, inaugurates a particular stage in history: the return of populism in the governments of Latin America (with strong nationalistic content).